2008
DOI: 10.3201/eid1412.070727
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovisInfection in Holstein Friesian Cattle, Iran

Abstract: To identify strains of Mycobacterium bovis circulating in Iran, we used region of difference, spoligotypes, and variable number tandem repeats to genotype 132 M. bovis isolates from Holstein Friesian cattle. Despite wide geographic origins, the strains were genetically homogeneous. Increased distribution of cattle herds and inadequate control measures may have contributed to strain dispersion. E stimates suggest that globally >50 million cattle are infected with Mycobacterium bovis, causing an annual loss of ≈… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
(9 reference statements)
6
14
0
Order By: Relevance
“…Mild lesions in lungs were found in only one slaughtered bovine. Similar observations were published in the United States and Iran, where no gross lesions suggestive of BTB were observed in lungs from dairy cattle, but frequently in lymph nodes of the thoracic region (Whipple et al, 1996;Tadayon et al, 2008). On the contrary, affection of lungs and other organs has been reported in cattle in Africa.…”
Section: Discussionsupporting
confidence: 85%
“…Mild lesions in lungs were found in only one slaughtered bovine. Similar observations were published in the United States and Iran, where no gross lesions suggestive of BTB were observed in lungs from dairy cattle, but frequently in lymph nodes of the thoracic region (Whipple et al, 1996;Tadayon et al, 2008). On the contrary, affection of lungs and other organs has been reported in cattle in Africa.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the prevalence of BTB in cattle from Tamaulipas that were exported to and slaughtered in The considerably higher prevalence for the year 1995 was expected because at that time, there were no activities focused in the control of BTB. After the reduction of the prevalence in 1996, there was a slightly rising of this pattern in subsequent years (1997 and 1998), which is consistent with the previously reported in other studies (PAHO, 1992;Tadayon et al, 2008;Demelash et al, 2009). The aforementioned increment is consequence of detecting as positive to skin test animals infected with other Mycobacterium spp.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding risk factors, the association between breed, specifically B. taurus genotypes, reported in this study, also has been reported by other authors (Kazwala et al, 2001;Ameni et al, 2007;Tadayon et al, 2008;Ngandolo et al, 2009). However, Elias et al (2008) stated that the breed of cattle is not associated with BTB.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…6 On the other hand, Iran is among the seven Asian States with an existing bovine TB control scheme operating at national scale with a very homogenous of bovine M. bovis. This appears in concordance with few previously reported observations 7 that cases of zoonotic TB in Iranian population is lower compared to its neighboring countries. 8 Different approaches to differentiate M. bovis from M. tuberculosis complex are done but the PCR-RFLP using OxyR gene is highly sensitive and inexpensive method.…”
Section: Introductionsupporting
confidence: 82%